Evidence on the Day-of-the-Week Effect and Asymmetric Behavior in the Bombay Stock Exchange - Chia, Ricky Chee-Jiun; Liew, Venus Khim-Sen (IUP Publications, 2010)
This study examines the existence of day-of.the~week effect and asymmetrical market behavior in the Bombay Stock Exchange (BSE) over the post-9/11 and post-9/11 sub-periods. This study found the existence of significant positive Monday effect and negative Friday effect during the pre-9/l1 sub-period. Further analysis using the EGARCH and EGARCH-M models revealed the asymmetrical market reaction to the positive and negative news in BSE. Moreover, significant day-of-the-week effect is found present in BSE regardless of sub-periods, after controlling for time-varying variance and asymmetrical market behavior.